New construction methodology-geothermal cogeneration plant efficiency improvements for environmental and economic sustainability using waste heat recovery system - Prakash Arul Jose, J; Rajesh Prasanna, P; Prakash, Fleming (International Journal of Engineering and Technology, 2018)
Power station is used in geothermal cogeneration or Combined Heat and Power (CHP) plant to generate electric power and heat from a single process simultaneously. Industrial CHP gains attention due to its sustainability and its nature of carbon footprint reduction. In this regard, CHP is more effective than generating steam or burning fuel on-site, and electricity is imported from the grid. CHP is a combined system which finds applications in several techniques and thermal and fuel systems, and these functionalities can be integrated into prevail-ing building structures. In CHP, the modifications are carried out with respect to the energy and user requirements. In heat recovery mecha-nism of CHP plant, several critical parameters are required. The present research work focuses on heat recovery analysis in geothermal co-generation (CHP) plant, in which the methods to lessen the generated secondary (waste) heat is emphasized by enhancing energy efficiency. Further it also includes passive and active strategies. The recent trends of direct electric conversion devices are more useful, and therefore can be introduced in industrial waste heat recovery applications, which are usually applied in CHP or geothermal cogeneration plants includ-ing paper mills and chemical processing and refinery systems, hotels, hospitals, industries and commercial structures, where constant heat and power requirements exist.Â Â